Investigation and plasma cleaning of first mirrors coated with relevant ITER contaminants: beryllium and tungsten. (23rd June 2017) - Moser, L.; Doerner, R.P.; Baldwin, M.J.; Lungu, C.P.; Porosnicu, C.; Newman, M.; Widdowson, A.; Alves, E.; Pintsuk, G.; Likonen, J.; Hakola, A.; Steiner, R.; et al.
Abstract: In order to extend the investigation of the plasma cleaning of ITER first mirrors, a set of molybdenum mirrors was coated in a laboratory with ITER-relevant contaminants, namely beryllium and tungsten. Different coating techniques as well as several contaminant compositions were used to ensure a large variety of films to clean, completing a previous study conducted on mirrors exposed in the JET ITER-like wall (tokamak deposits) [1 ]. Due to the toxicity of beryllium, the samples were treated in a vacuum chamber specially built for this purpose. The cleaning was performed using capacitively coupled RF plasma and evaluated by performing reflectivity measurements, scanning electron microscopy, x-ray photoelectron spectroscopy and ion beam analysis. The removal of all types of contaminants was achieved by using different plasma compositions (argon, helium and mixtures of the two) with various ion energies (from 200–600 eV) and in some cases the mirror's reflectivity was restored towards initial values. Pure helium discharges were capable of removing mixed beryllium/tungsten layers and oxidized molybdenum. In addition, no significant increase in the diffuse reflectivity of the mirrors was observed for the helium cleaning, though this was the case for some samples cleaned with argon. Helium is therefore appropriate for cleaning all mirrors in ITER leading to a possible cleaning regime where the entire vessel is filled with He and all mirrors are cleaned simultaneously without damaging their surfaces.